Modelagem de nanotubos de nitreto de gálio - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Nanotubes can be classified with respect to their symmetry in chiral and achiral (armchair and zigzag). Several methods have been used to nanotubes synthesis, thus it is expected that the structures obtained have different structural characteristics (diameter, length and wall thickness). In this work we studied single wall gallium nitride nanotubes, the models were obtained through winding a plane of atoms, using algorithms written in Shell Bash programming language for Linux. Two methods were used to generate the planes of gallium nitride. The first is based on graphene structure, where Ga and N atoms replaced the carbon atoms. The second is based on the plane (0001) of hexagonal phase from gallium nitride crystal (wurtzite). The optimization of atoms coordinates was made using the PM7 semiempirical method. It was observed that after optimization there was a small distortion at the edges of models to compensate the effects of free valences, reducing the Ga-N bond distance. The optimized coordinates were collected and used in ab initio calculations, Hartree-Fock (RHF) and Density Functional Theory (B3LYP) with the basis sets 3-21G, 6-31G, 6-31G(d, p) and 6-311G. The energy difference |HOMO-LUMO| was calculated, revealing that tis property is strongly linked to the geometry of the unsaturated nanotubes. Analyzing the density of states and the orbital contributions it was found that the achiral models show similar bands, however some orbitals between HOMO and LUMO decrease the band distance, for zigzag models. The Mulliken charges distribution and dipole moments have shown that the armchair structures are non-polar, while the zigzag structures are polar.
Keywords: Nitreto de Gálio; Nanotubos; Química teórica; Propriedades eletrônicas; Métodos mecânico-quânticos; Nanotubes; Gallium nitride; Theoretical chemistry; Electronic properties; Quantum mechanic methods; QUIMICA::FISICO-QUIMICA